If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5(2x + 5) = 19 Reorder the terms: 6x + -5(5 + 2x) = 19 6x + (5 * -5 + 2x * -5) = 19 6x + (-25 + -10x) = 19 Reorder the terms: -25 + 6x + -10x = 19 Combine like terms: 6x + -10x = -4x -25 + -4x = 19 Solving -25 + -4x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + -4x = 19 + 25 Combine like terms: -25 + 25 = 0 0 + -4x = 19 + 25 -4x = 19 + 25 Combine like terms: 19 + 25 = 44 -4x = 44 Divide each side by '-4'. x = -11 Simplifying x = -11
| 4(5a-2b)+6(3a-3b)= | | 18-r=43 | | f(x)=100(5)*x | | X+(5x)=120 | | 12.67+42.35x=5.34+26.25 | | 3x^2+100x=212 | | x+43=-16 | | 5(2x+4)=(9x+4) | | 9=-2X-5+B | | -4x-10x+5= | | 9x+4=-86 | | 7x+13x-4=5(4x-4) | | 9b+9b=72 | | -0.7+0.5+12x=0.5x+0.8 | | -1.2x+11+2.6x= | | 9x+4=86 | | 9X+3=3X | | 218=119-x | | 7.30=4x+6 | | 4r+3=10 | | 1.3x-5.4x-5.4x+3= | | 35-3x=10+6x | | 1.3h-4(2.3h-3)=2.3h-6 | | 5x+7y=300solvey | | 2(5z+2)-3(z+1)= | | -11r-3+12r+2= | | 0=2x^2-3x-104 | | x+x+3=31 | | 12x=10+2 | | z=(x-4)k | | 8r^3+24r^2=32r | | 2.2n+4-9-4.5n= |